Experiments on a visual servoing approach using disturbance observer - Lee, Joon-Soo; Suh, Il Hong; You, Bum-Jae; Oh, Sang-Rok (IEEE International Conference on Intelligent Robots and Systems, 1999)
A visual servoing method has been proposed based on disturbance observer to eliminate the effect of the off-diagonal component of image feature Jacobian, since performance indices such as measurement sensitivity of visual features, sensitivity of the control to noise, and controllability could be improved when an image feature Jacobian was given as a block diagonal matrix. In this paper, experimental results of disturbance observer-based visual servoing are discussed, where Samsung FARAMAN-AS1 6-axis industrial robot manipulator is employed. Also, the feature saturator is proposed to stabilize the disturbance observer loop by saturating the differential changes of the image features.